The Role of Volunteers and Political Participation in the 2012 Jakarta Gubernatorial Election - Ahmad Suaedy (Journal of Current Southeast Asian Affairs, 2014)
The changes that occurred in the Jakarta 2012 election may be seen as a change in Indonesia’s social movements and election tradition. They marked a social movement with special characteristics; specifically, a ‘partisan’ movement, led by the successful Jokowi–Ahok ticket. The partisan social movement also changed the tradition of money politics, which has always coloured general and local elections in Indonesia. This paper found four main factors in Jokowi–Ahok’s victory. The first was their reputations and track records of leadership and consistency, which, secondly, encouraged unpaid volunteers to motivate the public to participate in the election and vote for the pair. Thirdly, in contrast to previous social movements in Indonesia, the volunteers did not just work to overthrow the current leadership and replace it, and then distance themselves, but instead continued to monitor the candidates; some managed government directly, while others took watch dog position. Fourthly, the relationship between volunteers and local government was not necessarily oppositional. As such, they were partisan not only in that they were supporters of a pair of candidates, but also in their promotion and support of openness, anti-corruption efforts and provision of maximum public services.